Cap Polyposis Syndrome Imitating Inflammatory Bowel Disease with Polyps Extending to the Terminal Ileum - Garrett Thomas Coleman; Rawan Dayah; Suimin Qiu; Gurinder Luthra (Case Reports in Gastroenterology)
Introduction: Cap polyposis syndrome is a rare subtype of mucosal prolapse disease characterized by erythematous, inflammatory colonic polyps covered by a cap of fibrinopurulent mucous. Although a benign condition, patients may present with significant symptoms that can be suggestive of inflammatory bowel disease or colorectal cancer. Case Presentation: We describe the case of a 34-year-old male who presented with a 5-month history of diarrhea and 40-lb weight loss following hospitalization for enterotoxigenic Escherichia coli colitis. The patient had a past medical history significant for prior colonoscopy revealing hundreds of polyps and a father who died of colorectal cancer at age 45. Multiple repeat infectious stool workups were negative, and antibiotics failed to resolve the patient’s symptoms. The patient underwent endoscopy which revealed numerous polyps from the rectum to the terminal ileum that appeared similarly to pseudopolyps giving concern for inflammatory bowel disease. Subsequent histology demonstrated surface erosion and inflammation without dysplasia. Review of endoscopy showed inflammatory polyps with a cap of fibrinopurulent mucous. In the absence of chronic inflammation (C-reactive protein was within normal limits following hospitalization), endoscopic and histologic findings were suggestive of cap polyposis syndrome. Conclusion: Cap polyposis is diagnosed endoscopically and histologically. While most cases of cap polyposis are confined to the distal colon and rectum, we believe that this is the first case of cap polyposis syndrome extending to the terminal ileum. Treatment of cap polyposis syndrome is dependent on the severity of symptoms.